Low‐ and high‐risk human papillomavirus genotype infections in intra‐anal warts in HIV‐positive men who have sex with men. (1st October 2016) - Siegenbeek van Heukelom, M.L.; Richel, O.; Vries, H.J.C.; Sandt, M.M.; Beck, S.; Munckhof, H.A.M.; Pirog, E.C.; Koning, M.N.C.; Prins, J.M.; Quint, K.D.
Summary: Background: Anogenital warts are often presumed to represent nondysplastic or low‐grade anal intraepithelial neoplasia (LGAIN). We previously demonstrated that up to 20% of intra‐anal warts in HIV‐positive men who have sex with men (MSM) contain regions of high‐grade AIN (HGAIN). Objectives: To determine the causative human papillomavirus (HPV) types of low‐ and high‐ grade dysplastic areas in warts from HIV‐positive MSM. Methods: A total of 42 intra‐anal warts from 41 HIV‐positive MSM were graded as nondysplastic, LGAIN or HGAIN. Whole‐tissue sections (WTS) were analysed with the SPF10 polymerase chain reaction/LiPA25 HPV genotyping system. If the WTS contained multiple HPV types, dysplastic regions were isolated by laser capture microdissection (LCM) for HPV genotyping. Results: Overall, 38 of 42 (91%) WTS tested positive for HPV DNA. Of these, 23 (61%) contained a single HPV type and 15 (39%) contained multiple HPV types. All LCM‐selected regions contained no more than one HPV type. Ten of 42 (24%) WTS contained HGAIN disease, of which six (60%) were associated with a high‐risk HPV (hrHPV) genotype. Twenty‐three of 42 WTS contained LGAIN disease, of which two (9%) were associated with hrHPV. AIN lesions containing hrHPV types were identified using p16 staining. Conclusions: LGAIN lesions can be caused by high‐risk HPV genotypes and vice versa. We therefore recommend routine follow‐up and treatment of all dysplastic intra‐anal warts for HIV‐positive MSM.